Monoclonal gammopathy of ocular significance (MGOS) – a short survey of corneal manifestations and treatment outcomes. Issue 4 (21st March 2022) - Garderet, Laurent; Al Hariri, Mohammad; Wasielica-Poslednik, Joanna; Munder, Markus; Kormányos, Kitti; Pena, Camila; Gozzetti, Alessandro; Zhou, Xiang; Waszczuk-Gajda, Anna; Rosinol, Laura; Mikala, Gabor; Krzystanski, Mateusz; et al.
Abstract: Monoclonal gammopathy of ocular significance (MGOS) is a rare subset of monoclonal gammopathy of clinical significance occurring secondary to plasma cell disorders and causing ocular manifestations. We identified 23 patients with paraproteinemic keratopathy (PPK) in the setting of monoclonal gammopathy of unknown significance (MGUS, 10), smoldering multiple myeloma (SMM, 3) or multiple myeloma (MM, 10). Many of these patients with PPK (11/23) presented decreased vision. All patients with MM and 40% of those with other diagnoses such as SMM and MGUS received systemic therapy with or without autologous stem cell transplantation. Four eyes of four patients were treated by penetrating keratoplasty. In most cases, neither ocular nor hematologic treatment afforded a durable improvement in the visual acuity (recurrence after a median of 11 months), despite initial responses. Further studies will be required to determine the optimal strategy to treat and prevent the relapse of ocular symptoms in patients with PPK.